2005
DOI: 10.1002/elps.200410221
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis hyphenated to inductively coupled plasma-sector field-mass spectrometry for the detection of chromium species after incubation of chromium in simulated sweat

Abstract: The presence of chromium in chromium-tanned leather represents a considerable health problem since it can lead to chronic allergic contact dermatitis. Apart from trivalent chromium (Cr(III)), which is used for tanning, leather often contains hexavalent chromium (Cr(VI)), resulting from the oxidation of Cr(III) during the tanning process. This study deals with the chromium compounds in simulated sweat when brought into contact with Cr(III) or Cr(VI) and with chromium-tanned leathers. A capillary electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…During the tanning process this species can be oxidized and chromium(VI), a well-known contact allergen, can be formed. In their paper, van Lierde et al [187] investigated the chromium species detectable after incubation of simulated sweat with chromium(III) and (VI) as well as tanned leather. In their experiments they used CE coupled to a high-resolution sector field ICP-MS. Lactic acid and methionine could be identified as the substances mainly responsible for the reduction and complexation of chromium in artificial sweat.…”
Section: Applications Of Ce-icp-msmentioning
confidence: 99%
“…During the tanning process this species can be oxidized and chromium(VI), a well-known contact allergen, can be formed. In their paper, van Lierde et al [187] investigated the chromium species detectable after incubation of simulated sweat with chromium(III) and (VI) as well as tanned leather. In their experiments they used CE coupled to a high-resolution sector field ICP-MS. Lactic acid and methionine could be identified as the substances mainly responsible for the reduction and complexation of chromium in artificial sweat.…”
Section: Applications Of Ce-icp-msmentioning
confidence: 99%
“…The release properties of selenium from the CS-SeNPs was studied in the following release media: (1) Simulated sweat fluid (pH 6.3) was composed of 65 mM NaCl, 5 mM KCl, 9 mM lactic acid sodium salt, and 22 mM urea (Van Lierde, Chéry, Moens, & Vanhaecke, 2005); (2) Simulated gastric fluid was composed of HCl solution (pH 1.2) with 0.1% (w/v) pepsin; (3) Simulated intestinal fluid was composed of PBS (pH 7.4) with 1.0% (w/v) pancreatin . The release rate was determined by incubation of known amounts of CS (l, h)-SeNPs solutions in sealed tubes with 10 mL of the release media at a stirring speed of 100 rpm and a temperature of 37 °C.…”
Section: Measurement Of Controlled Release Efficiencymentioning
confidence: 99%
“…291 other Cr species extracted from chromium-tanned leather in simulated sweat. 293 It could be shown that the amino acid methionine is responsible for the reduction of Cr(VI) into Cr(III), which, in turn, forms a complex with lactic acid. In a subsequent study, the setup was also used in in vitro permeation studies with porcine and human skin to study the factors affecting permeation.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidsmentioning
confidence: 99%